Unraveling the Dissolution‐Mediated Reaction Mechanism of α‐MnO2 Cathodes for Aqueous Zn‐Ion Batteries. Issue 48 (9th November 2020) - Kim, Sung Joo; Wu, Daren; Sadique, Nahian; Quilty, Calvin D.; Wu, Lijun; Marschilok, Amy C.; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Zhu, Yimei
Abstract: Aqueous Zn/α‐MnO2 batteries have attracted immense interest owing to their high energy density, low cost, and safety, making them desirable for future large‐scale energy application. Despite these merits, the comprehensive understanding of their reaction mechanism has been elusive due to the limitations of standard bulk characterization. Here, via transmission electron microscopy, the dissolution‐mediated reaction mechanism of a Zn/α‐MnO2 system is discovered and explored in full scope to involve reversible formation of Zn4 SO4 (OH)6 · x H2 O and "birnessite‐like" Zn‐MnO x phase upon cycling. Overall, α‐MnO2 acts primarily as a source for cell activation through dissolution and thus is not directly involved in the Zn redox chemistry. This microscopic study offers a unique knowledge on the unconventional reaction chemistry of Zn/α‐MnO2 batteries. Abstract : Via transmission electron microscopy, the dissolution‐mediated reaction mechanism of a Zn/α‐MnO2 system for aqueous zinc‐ion batteries is discovered to form Zn4 SO4 (OH)6 · x H2 O that undergoes reversible formation with "birnessite‐like" Zn‐MnO x upon electrochemical cycling. α‐MnO2 acts primarily as a source for cell activation through dissolution that happens from the surface likely promoted by guest ion insertion at the surface.